2022
DOI: 10.1371/journal.pone.0266666
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the differences in Caesarean section (C-section) rates between public and privately insured mothers in Florida: A decomposition approach

Abstract: Background Caesarean section (C-sections) is a medically critical and often life-saving procedure for prevention of childbirth complications. However, there are reports of its overuse, especially in women covered by private insurance as compared to public insurance. This study evaluates the difference in C-Section rates among nulliparous women in Florida hospitals across insurance groups and quantifies the contribution of maternal and hospital factors in explaining the difference in rates. Methods We used Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…The prevalence of caesarean section in the public and private insured mothers in Florida by Puro N et al was estimated as 18.87% [19]. This was lower than that gotten from our study which was 29.6%.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…The prevalence of caesarean section in the public and private insured mothers in Florida by Puro N et al was estimated as 18.87% [19]. This was lower than that gotten from our study which was 29.6%.…”
Section: Discussioncontrasting
confidence: 75%
“…This was lower than that gotten from our study which was 29.6%. The study revealed that higher rate of caesarean section was associated with diabetes, hypertension and expectant mothers being over 35 years [19]. However, the caesarean rate across the United States was approximately 32% [19].…”
Section: Discussionmentioning
confidence: 96%
“…Another study conducted in Egypt found similar rates of CS in government and private facilities, with rates of 35% and 36%, respectively. However, the study noted that there were differences in the characteristics of women who gave birth in government and private facilities, with women in private facilities being more likely to have higher education and higher income [ 20 ]. Overall, while the rates of CS may be similar in government and private health facilities, it is important to note that there may be differences in the reasons for performing CS and the characteristics of women who give birth in these facilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important finding is the difference in delivery method between the study and control groups in Koseoglu et al’s study [ 25 ], as it suggests that the two groups may not have been entirely comparable. Cesarean section rates can be influenced by various factors, such as maternal age, gestational age, and underlying medical conditions, and these factors may also be related to the outcome of interest [ 30 ]. Therefore, it is possible that the difference in the delivery method may have contributed to any observed differences in the outcome between the study and control groups.…”
Section: Discussionmentioning
confidence: 99%